Kompetensi Kewirausahaan Ditinjau Dari Perilaku Belajar Dan Motivasi Belajar Praktik Kewirausahaan Pada Mahasiswa Program Studi Pendidikan Akuntansi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Angkatan Tahun 2013 - Rustiana, Iin; , Drs Sudarto, M.M (2016)
The purpose of this research is to know the contribution of students learning behavior and learning motivation towards intrepreneurship competence on Accounting Education Student teacher training and education facultyin Muhammadiyah University of Surakarta. This type of research is quantitative asiosatif. The population in this research is accounting education Muhammadiyah University of Surakarta force by 2013 which amounts to 200 students with a sample of 127 students were taken with proportional random sampling techniques. The technique of data collection by using methods now that it has been tested with test validity and reliability tests. Data analysis technique used is multiple regression, t-test, f-test, the relative contribution and effective contribution. The conclusion that can be drawn from this study are: 1) there was significant influence between the learning behaviors towards entrepreneurial competence based on t-test, namely > obtained at 2,186 > 1,979 and significant value < 0.05 0.025, i.e. 2) there was significant influence between the motivation of learning the entrepreneurial competence based on test against t obtained at >, namely 2.919 > 1.979 and significant value < i.e. 0.05 0.025.3) there was significant influence between the learning behaviors and the learning motivation of entrepreneurial competencies based on tests against F known F count > F table 78,878 > 3,069 with significant value is 5%. The results of calculations for the value of the retrieved 56% competence of entrepreneurship is influenced by the behavior and the balance leraned motivation 44% is affected by other variables not examined in this study.